Japanese native speakers' perception of Brawijaya University Japanese Language Education Students' intonation pronunciation of Aizuchi Soudesuka - 'Aisy, Naura Rohadatul (Universitas Dian Nuswantoro, 2023)
This study uses a qualitative approach by presenting data descriptively. This study aims to determine how Japanese native speakers perceive Japanese learners' soudesuka’s intonation pronunciation. Three Japanese native speakers participated in this study and have assessed the pronunciation of Japanese learners' aizuchi soudesuka intonation. The findings showed that nine out of ten respondents can pronounce soudesuka which means “understand,” with the correct descending intonation; only three out of ten respondents can pronounce soudesuka which means “asking question,” with the right ascending intonation; and six out of ten respondents can pronounce soudesuka which means “happy, joy, or surprise” with the right descending intonation. The results of this study indicate that, according to Japanese native speakers, respondents tend to be more able to pronounce soudesuka with descending intonation than soudesuka with ascending intonation.